Biochemical analysis of leptospiral LPS explained the difference between pathogenic and non-pathogenic serogroups. (March 2021) - Vanithamani, Shanmugam; Akino Mercy, Charles Solomon; Kanagavel, Murugesan; Sumaiya, Krishnamoorthi; Bothammal, Palanisamy; Saranya, Perumal; Prasad, Muthu; Ponmurugan, Karuppiah; Muralitharan, Gangatharan; Al-Dhabi, Naif Abdullah; Verma, Ashutosh; Vijayachari, Paluru; et al.
Abstract: Lipopolysaccharide (LPS) is the major surface antigen of Leptospira . In this study, the genes involved in the LPS biosynthesis were analyzed and compared by bioinformatics tools. Also, the chemical composition analysis of leptospiral lipopolysaccharides (LPS) extracted from 5 pathogenic serovars like Autumnalis, Australis, Ballum, Grippotyphosa, Pomona, and the nonpathogenic serovar Andamana was performed. Methods used were Limulus amebocyte lysate assay (LAL), gas chromatography-mass spectrometry (GC-MS), fourier transform infrared spectroscopy (FT-IR), and nuclear magnetic resonance spectroscopy (NMR). LAL assay showed a significantly higher level of endotoxicity among pathogenic serovars (~0.490 EU/mL) than that of nonpathogenic Andamana (~0.102 EU/mL). FAMES analysis showed the presence of palmitic acid (C16:0), hydroxy lauric acid (3-OH-C12:0), and oleic acid (C18:0). Palmitoleic acid (C16: 1), and 3- hydroxy palmitate (3-OH-C16:0) was detected only in pathogenic serovars. In contrast myristoleic acid (C14:1) and stearic acid (C18:0) were present in Andamana. FTIR analysis revealed C–O–C stretch of esters, 3°ROH functional groups and carbohydrate vibration range were similar among pathogenic serovars. The NMR analysis reveals similarity for 6 deoxy sugars and methyl groups of Autumnalis, Australis, and Ballum. Further, the presence of palmitoleic acid and 3-hydroxy palmitate may be the significant pathogen-associated predisposing factor. This mediates high osmolarity glycerol (HOG) mediated stress response in leptospiral LPS mediated pathogenesis. Highlights: The biochemical compositions of LPS were compared among pathogenic and non-pathogenic serovars. S. cerevisiae model system was used to describe the LPS mediated pathogenesis. The LPS mediated TLR2, TLR4 and P38 expression of THP1 cells were assessed by Real-time qPCR assay. The genes involved in the biosynthesis of Leptospira lipopolysaccharide (LPS) were identified and compared using the NCBI and KEGG pathway databases.